Pengaruh Kepemimpinan Situasional Kepala Sekolah Terhadap Kepuasan Kerja Guru Di SMA Negeri 1 Siborongborong - Lastiar Magdalena Nababan; Lasmaria Lumbantobing; Robinhot Sihombing (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
The purpose of this research is to determine the influence of the principal's situational leadership on teacher job satisfaction at SMA Negeri 1 Siborongborong. The method used in this research is an inferential quantitative method. The population is all teachers at SMA Negeri 1 Siborongborong, North Tapanuli Regency in 2023, totaling 83 people and this research is a population study. Data was collected using a positive closed questionnaire with 30 items. The results of the data analysis show that there is an influence of the principal's situational leadership on teacher job satisfaction at SMA Negeri 1 Siborongborong: 1) Test the analysis requirements: a) test the positive influence obtained by the value rxy = 0.488 > rtable(=0.05,n=83 ) = 0.213, thus it is known that there is a positive influence between variable significant relationship between variable b) Regression coefficient of determination test (r2) = 23.8%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable, namely 25.353 > 4.00. Thus Ha is accepted and H0 is rejected.